2009
DOI: 10.1108/09590550910966196
|View full text |Cite
|
Sign up to set email alerts
|

Store format choice and shopping trip types

Abstract: Purpose: The purpose of the paper is to identify store format attributes that impact on store format choice when consumers conduct fill-in or major trips to buy groceries. By doing so, we take into consideration that consumers patronise multiple (store-based) formats depending on the shopping situation operationalised by the type of shopping trip.Design/methodology/approach: The paper adopts the conceptual framework of random utility theory via application of a multinomial logit modelling framework. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 44 publications
6
81
0
3
Order By: Relevance
“…This is particularly true for consumers of a higher age and those who shop at grocery stores more often. We thus identify the relevance of shopper logistics in a grocery retail setting for elderly and frequent shoppers and thereby confirm work by Keillor et al (1996), Meneely et al (2009), Reutterer and Teller (2009) and Teller and Gittenberger (2011).…”
Section: -------------------------Table 3 Near Here -----------------supporting
confidence: 72%
See 1 more Smart Citation
“…This is particularly true for consumers of a higher age and those who shop at grocery stores more often. We thus identify the relevance of shopper logistics in a grocery retail setting for elderly and frequent shoppers and thereby confirm work by Keillor et al (1996), Meneely et al (2009), Reutterer and Teller (2009) and Teller and Gittenberger (2011).…”
Section: -------------------------Table 3 Near Here -----------------supporting
confidence: 72%
“…Particular temporal and spatial aspects of shopping in terms of distance or accessibility have received considerable attention since seminal work from Reilly (1931) and Huff (1964), for example Fotheringham (1988), Grace and O'Cass (2005), Pan and Zinkhan (2006) and Reutterer and Teller (2009). Some other authors have focussed on convenience by providing infrastructural services (e.g.…”
Section: Store-based Retailingmentioning
confidence: 99%
“…It has been demonstrated that shoppers prefer to visit hypermarket to conduct major trips while supermarkets are preferred for fill-in trips (Reutterer & Teller, 2009). At the same time,…”
Section: Originality Limitations and Future Researchmentioning
confidence: 99%
“…The attribute retail tenant mix as consequence of the application of the 'macro marketing mix' on an agglomeration level is influenced by attributes resulting out of the application of the 'micro marketing mix' on a store level (Hart, 2009). According to the store patronage literature such (store) attributes are accessibilityincluding manoeuvrability/orientation, parking conditions -merchandise value, the product range and sales personnel (e.g., Reutterer & Teller, 2009;Severin et al, 2001). Furthermore, the non retail element can be seen as a complement and a positive driver of the perception of the retail element of an agglomeration (Dennis et al, 2005;Whyatt, 2004;Wakefield and Baker, 1998).…”
Section: (Infra-)structure Of Urban Retail Agglomerationsmentioning
confidence: 99%